Cystic Endometrial Hyperplasia and Pyometra Complex in a Bitch - Gangwar, Kavisha; Yadav, Brijesh Kumar; Gangwar, Neeraj Kumar; sachan, vikas (The Indian Journal of Animal Reproduction, 2023)
A 11 years old German Shepherd bitch with the history of abdominal distension, vomiting, and purulent vaginal dis charge was presented to Veterinary Clinical Complex, DUVASU, Mathura. Haematological examination revealed  increase in total erythrocyte count and total leucocyte count while decrease in platelet count. The condition was treated  with ovariohysterectomy and histopathological examination revealed the condition as cystic endometrial hyperplasia  with pyometra complex.
Keywords: Bitch; Cystic Endometrial Hyperplasia; Pyometra; ovariohysterectomy